Impact of respiratory infection in the results of cardiac surgery in a tertiary hospital in Brazil - Isaac Newton Guimarães Andrade (Brazilian Journal of Cardiovascular Surgery, 2015)
AbstractObjective:To assess the impact of respiratory tract infection in the postoperative period of cardiac surgery in relation to mortality and to identify patients at higher risk of developing this complication.Methods:Cross-sectional observational study conducted at the Recovery of Cardiothoracic Surgery, using information from a database consisting of a total of 900 patients operated on in this hospital during the period from 01/07/2008 to 1/07/2009. We included patients whose medical records contained all the information required and undergoing elective surgery, totaling 109 patients with two excluded. Patients were divided into two groups, WITH and WITHOUT respiratory tract infection, as the development or respiratory tract infection in hospital, with patients in the group without respiratory tract infection, the result of randomization, using for the pairing of the groups the type of surgery performed. The outcome variables assessed were mortality, length of hospital stay and length of stay in intensive care unit. The means of quantitative variables were compared using the Wilcoxon and student t-test.Results:The groups were similar (average age P=0.17; sex P=0.94; surgery performed P=0.85-1.00) Mortality in the WITH respiratory tract infection group was significantly higher (P<0.0001). The times of hospitalization and intensive care unit were significantly higher in respiratory tract infection (P<0.0001). The presence of respiratory tract infection was associated with the development of other complications such as renal failure dialysis and stroke P<0.00001 and P=0.002 respectively.Conclusion:The development of respiratory tract infection postoperative cardiac surgery is related to higher mortality, longer periods of hospitalization and intensive care unit stay.